Effects of sequential cleavage and blastocyst embryo transfer on pregnancy outcomes in patients with poor ovarian response. (February 2023) - Hu, Yu-Ling; Wang, Yue; Geng, Li-Hong; Meng, Xiang-Qian; Xu, Hai-Jiao; Adu-Gyamfi, Enoch Appiah; Zhong, Zhao-Hui; Wan, Qi; Ding, Yu-Bin
Abstract: The management of patients with poor ovarian response (POR) remains a major challenge for fertility specialists in in vitro fertilization-embryo transfer (IVF-ET). In this retrospective cohort study, we aimed to evaluate the clinical effect of sequential transfer on pregnancy outcomes in patients with POR. A total of 3579 POR patients who underwent the first frozen embryo transfer (FET) cycle were enrolled from January 2018 to April 2021. The patients were divided into three groups according to the embryo transfer (ET) strategy adopted: a study group that included POR patients in whom a cleavage-stage embryo (day 3) and a blastocyst (day 5/6) were transferred (sequential transfer group), and two control groups in whom two cleavage-stage embryos (D3-dET group) or two blastocysts (D5/6-dET group) were transferred. The study group was matched with the control groups at a ratio of 1:4 by propensity score matching (PSM). The main pregnancy outcomes measured were the live birth rate and multiple pregnancy rate. After PSM, the live birth rate in the sequential transfer group was significantly higher than that in the D3-dET group (44.2% vs. 34.3%, P = 0.019), and was similar to that in the D5/6-dET group (44.2% vs. 45.3%; P = 0.90). In addition, there was no increase in the risk of multiple pregnancy among POR patients undergoing sequential transfer compared with both D3-dET (26.7% vs. 25.6%, P = 0.85) and D5/6-dET (26.7% vs. 28.4%, P = 0.97) groups. These findings imply that sequential transfer is an effective option for POR patients and could be utilized after careful consideration. Highlights: This is the first study to examine the effectiveness of sequential embryo transfer in patients with poor ovarian response. Sequential transfer resulted in a higher live birth rate compared with the double cleavage-stage embryo transfer. Sequential embryo transfer and double blastocyst transfer had similar live birth rates.